2009
DOI: 10.4049/jimmunol.0803730
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Tumor Progression Locus 2 Promotes a Type 2 Th Cell Response in Ovalbumin-Immunized Mice

Abstract: The protein kinase encoded by the Tpl2 proto-oncogene regulates ERK activation and cytokine gene expression in macrophages in response to LPS and TNF-α. In this study we show that OVA-immunized Tpl2−/− mice express high levels of IgE and develop more severe bronchoalveolar eosinophilic inflammation than Tpl2+/+ controls, when challenged with OVA intranasally. Bronchoalveolar exudates and supernatants of OVA-stimulated splenocytes from immunized Tpl2−/− mice express elevated levels of IL-4 and IL-5, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 54 publications
4
38
2
Order By: Relevance
“…Negative feedback regulation between Th subsets may explain this phenotype, whereby decreased Th1 differentiation in absence of TPL-2 results in increased Th2 polarization. It has been suggested that defective TCR-mediated activation of ERK in Tpl2 −/− CD4 + T cells results in reduced T-bet and Stat4 expression, and consequently in reduced Th1 differentiation [77]. However, the reduction in TCRinduced ERK phosphorylation in TPL-2-deficient cells is relatively modest and it is possible that TPL-2 has other signaling functions in Th1 differentiation.…”
Section: Regulation Of Immune and Inflammatory Responses By Tpl-2mentioning
confidence: 61%
See 3 more Smart Citations
“…Negative feedback regulation between Th subsets may explain this phenotype, whereby decreased Th1 differentiation in absence of TPL-2 results in increased Th2 polarization. It has been suggested that defective TCR-mediated activation of ERK in Tpl2 −/− CD4 + T cells results in reduced T-bet and Stat4 expression, and consequently in reduced Th1 differentiation [77]. However, the reduction in TCRinduced ERK phosphorylation in TPL-2-deficient cells is relatively modest and it is possible that TPL-2 has other signaling functions in Th1 differentiation.…”
Section: Regulation Of Immune and Inflammatory Responses By Tpl-2mentioning
confidence: 61%
“…In vitro experiments suggest that IgE switching of purified splenic B cells induced by CD40 plus IL-4 requires TPL-2 activation of ERK [35]. However, IgE antibody production is not defective in Tpl2 −/− mice, possibly due to enhanced Th2 cell differentiation (see above), increasing the available concentration of IL-4, which promotes switching to IgE [77]. Analysis of B cells purified from TPL-2-deficient Nfκb1 −/− mice has also suggested that TLR4 utilizes TPL-2 to activate ERK in B cells [82].…”
Section: Regulation Of Immune and Inflammatory Responses By Tpl-2mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, TPL2 ablation in mice ameliorates the severity of a variety of inflammatory pathologies (1,6), suggesting that it could be explored as a therapeutic target. In contrast, however, TPL2-deficient mice show increased susceptibility to infection with the T helper 1 (Th1)-inducing parasite T. gondii (7) and ovalbumin-induced bronchoalveolar inflammation (8) because of a T-cell intrinsic defect rather than an altered innate immune response, highlighting cell type-and stimulus-dependent roles for TPL2 in the immune system.…”
mentioning
confidence: 92%